A diverse and specific Phytophthora infestans sensu lato population associated with Solanum betaceum in southern Colombia (2011)
New populations within the genus Phytophthora, associated with late blight have been reported in recent years. In South America, the presence of P. andina associated with native and exotic plants, among which is tree tomato (Solanum betaceum), have been described as the result of the complex process of evolution of these plant pathogens. In the present study nuclear, mitochondrial sequences and SSR markers were used to determine the genetic diversity and structure of Phytophthora samples collected from S.betaceum crops in the Nariño and Putumayo departments. In addition, detached leaf assays were used to test aggressiveness of the strains on several cultivars of the host. Our results showed a P. infestans sensu lato population characterized by a high genetic diversity with individuals showing different levels of ploidy and high clonality, supported by the presence of only the A1 mating type. Isolates showed a high specificity to the host with a wide range of aggressiveness that could not be related to the genetic variation found. Ancestral polymorphism, as a result of cultural conditions of the host and an ongoing hybridization process in the region were suggested as hypothesis to explain the variation found. Results of this study contribute to the understanding of the evolutionary mechanisms associated with P. infestans sensu lato innative hosts.